2000
DOI: 10.1080/00288330.2000.9516924
|View full text |Cite
|
Sign up to set email alerts
|

Transport and attenuation of bacteria and bacteriophages in an alluvial gravel aquifer

Abstract: The relative attenuation of rhodamine WT dye, two strains of Escherichia coli, Bacillus subtilis endospores, and the F-RNA bacteriophage MS2 in an alluvial gravel aquifer was investigated in two tracing experiments at Burnham, near Christchurch, New Zealand. A simulated concentration curve was fitted to the observed breakthrough curves using the contaminant transport model AT123D, by optimising hydraulic conductivity (K), longitudinal dispersivity (α x ), and a removal constant (λ) (which includes die-off and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 24 publications
6
35
1
Order By: Relevance
“…This approach was demonstrated to be effective at simulating observed large exclusion effects (bacterial velocities nearly double that of conservative tracers) with minimal truncation (on the order of 5%) of the dispersive displacement distribution. This approach also leads to decreased apparent dispersion of the bacteria relative to conservative tracers, consistent with theoretical considerations and observations [116].…”
Section: Size Exclusionsupporting
confidence: 68%
See 2 more Smart Citations
“…This approach was demonstrated to be effective at simulating observed large exclusion effects (bacterial velocities nearly double that of conservative tracers) with minimal truncation (on the order of 5%) of the dispersive displacement distribution. This approach also leads to decreased apparent dispersion of the bacteria relative to conservative tracers, consistent with theoretical considerations and observations [116].…”
Section: Size Exclusionsupporting
confidence: 68%
“…They observed faster velocities of the bacteria relative to inert tracers, and estimated total removal rates of 2.4-9.4 day À1 . Sinton et al [116] further examined the apparent velocities of microbial (bacteria and virus) and inert tracers, and found that apparent velocity increased, and apparent dispersion decreased, with increasing particle size.…”
Section: Previous Field-scale Bacterial Transport Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of sorption was absent in the E. coli strains obtained from the Rotterdam Zoo in the work of Foppen et al (2010). In addition, Foppen and Schijven (2006) reported that, based on a number of studies, equilibrium sorption in E. coli transport was of little significance (Pang et al, 2003;Powelson and Mills, 2001;Sinton et al, 1997;Sinton et al, 2000;Alexander and Seiler, 1983;Havemeister and Riemer, 1985, both in: Matthess et al, 1985and in Matthess et al, 1988Champ and Schroeter, 1988;Merkli, 1975). Although the role equilibrium sorption plays in most of the strains we used in this work was indeed also rather limited, the role of kinetic attachment was at least equally limited.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the large number of studies investigating virus and bacterial transport, very few studies were conducted using bacterial spores. Sinton et al (2000) used pore size exclusion to explain the transport retardation of rhodamine WT dye, followed by MS2, Bacillus subtilis spores, E. coli J6-2, and E. coli 2690. Schijven et al (2003) found that MS2 and Clostridium bifermentans spores can travel greater distances than Escherichia coli (E. coli).…”
Section: Introductionmentioning
confidence: 99%